“Enhancing Artistic Expression in Grades 5–7 Visual Arts Lessons through Interactive Apps” - Axmedov Dilmurod Xolmamatovich (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article investigates the use of interactive applications in grades 5–7 visual arts lessons to enhance students’ artistic expression, creativity, and engagement. The study demonstrates that interactive apps, including digital drawing tools, animation software, and visual simulation platforms, enable students to experiment with artistic techniques, develop their skills, and express their ideas creatively. Integrating interactive apps into visual arts education promotes independent learning, collaboration, and critical thinking, providing an innovative approach to modern art instruction.